Tax Avoidance: The Role of Size and Intensity of Indonesian Manufacturing Sector (2021-2024) - Anisa Fitriani Shaqira; Iwan Sidharta; Sana Sholihah (Journal of Economics, Management, and Entrepreneurship, 2025)
Tax avoidance is an important issue that impacts state revenue, particularly in the manufacturing sector, which contributes significantly to the national economy. This study aims to verify the influence of company size and capital intensity on tax avoidance among manufacturing firms for the period of 2021-2024 at Indonesian Stock Exchange. The research employs a quantitative verifiable method with a panel data approach. Sampling is conducted using purposive sampling techniques targeting manufacturing companies that meet the research criteria. Data analysis is performed using panel data model testing, classical assumption tests, and multiple linear regression. The findings reveal that company size does not have a notable impact, while capital intensity demonstrates a significant positive effect on tax avoidance. This suggests that as the ratio of fixed assets rises, firms are presented with more opportunities to utilize tax avoidance tactics via effective management of depreciation. The results indicate that that as the proportion of fixed assets increases, companies have greater opportunities to employ tax avoidance strategies through depreciation management. These findings have implications for tax authorities and corporate management to consider internal factors influencing tax compliance, promoting a fairer, more transparent, and sustainable tax system.